2023
DOI: 10.1038/s41598-023-34771-y
|View full text |Cite
|
Sign up to set email alerts
|

Regional long-term analysis of dietary isotopes in Neolithic southeastern Italy: new patterns and research directions

Abstract: Isotopic analyses of prehistoric diet have only recently reached the threshold of going beyond site-focused reports to provide regional syntheses showing larger trends. In this work we present the first regional analysis for Neolithic southeastern Italy as a whole, including both substantial original data and a review of the available published data. The results show that dietary isotopes can shed new light on a number of traditional and important questions about Neolithic foodways. First, we observe regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…An additional caveat to interpreting differences between Northern and Southern Europe, however, is the variability in nitrogen enrichment between Atlantic and Mediterranean archaeological specimens of fish stemming from ecological differences between both marine contexts 161 . Likewise, the general picture of reliance on terrestrial resources by early farmers has long been confirmed by a series of palaeodietary studies 75 , 77 , 78 , even among groups living in coastal regions of southern and northern Italy 74 , 162 . Archaeological evidence also shows that the early farmers of the central Mediterranean, as might be expected, relied on the typical range of South-West Asian domesticated plants and animals 163 – 165 , but with regional variation in choice of livestock and crops 166 168 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…An additional caveat to interpreting differences between Northern and Southern Europe, however, is the variability in nitrogen enrichment between Atlantic and Mediterranean archaeological specimens of fish stemming from ecological differences between both marine contexts 161 . Likewise, the general picture of reliance on terrestrial resources by early farmers has long been confirmed by a series of palaeodietary studies 75 , 77 , 78 , even among groups living in coastal regions of southern and northern Italy 74 , 162 . Archaeological evidence also shows that the early farmers of the central Mediterranean, as might be expected, relied on the typical range of South-West Asian domesticated plants and animals 163 – 165 , but with regional variation in choice of livestock and crops 166 168 .…”
Section: Discussionmentioning
confidence: 91%
“…δ 13 C (‰) Mean ± s.d. δ 15 N (‰) References Upper Palaeolithic 41 − 19.41 ± 0.42 10.56 ± 1.40 57 66 Mesolithic 31 − 19.49 ± 0.94 10.01 ± 1.52 59 , 60 , 62 , 66 70 Neolithic 257 − 19.56 ± 0.51 9.25 ± 1.48 70 78 Copper Age 288 − 19.51 ± 0.58 10.66 ± 2.07 71 , 75 , 79 – 83 Bronze Age 239 − 17.94 ± 2.52 8.98 ± 1.26 11 , 71 , 75 , 84 – 89 Roman 640 − 19.08 ± 0.66 10.32 ± 1.63 90 94 Medieval 490 − 18.83 ± 1.09 8.97 ± 1.45 90 93 , 95 97
Figure 3
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to investigate post-mortem histories at a histological level in tandem with macroscopic taphonomic analysis. Many individuals from these sites have been the subject of multi-isotopic analyses investigating dietary practices and residential mobility [ 79 – 83 ]. For 29 of the individuals included in this study, corresponding 87 Sr/ 86 Sr isotopic measurements from bone and/or enamel were available [ 82 , 83 ] ( S1 File ).…”
Section: Methodsmentioning
confidence: 99%
“…Many individuals from these sites have been the subject of multi-isotopic analyses investigating dietary practices and residential mobility [ 79 – 83 ]. For 29 of the individuals included in this study, corresponding 87 Sr/ 86 Sr isotopic measurements from bone and/or enamel were available [ 82 , 83 ] ( S1 File ). These provide a proxy of geological origins and later life locality [ 84 , 85 ].…”
Section: Methodsmentioning
confidence: 99%